Mechanism of circADD2 as ceRNA in Childhood Acute Lymphoblastic Leukemia - Zhu, Yuting; Ma, Xiaopeng; Zhang, Heng; Wu, Yijun; Kang, Meiyun; Fang, Yongjun; Xue, Yao (Frontiers in Cell and Developmental Biology, 2021)
Background: Acute lymphocytic leukemia (ALL) is the most common malignant tumor in children. Increasing evidence suggests that circular RNAs (circRNAs) play critical regulatory roles in tumor biology. However, the expression patterns and roles of circRNAs in childhood acute lymphoblastic leukemia (ALL) remain largely unknown. Methods: circADD2 was selected by microarray assay and confirmed by qRT-PCR; in vitro effects of circADD2 were determined by CCK-8 and flow cytometry; while mice subcutaneous tumor model was designed for in vivo analysis. RNA immunoprecipitation and dual-luciferase assay were applied for mechanistic study. Protein levels were examined by Western blot assay. Results: circADD2 was down-regulated in ALL tissues and cell lines. Overexpression of circADD2 inhibited cell proliferation and promoted apoptosis both in vitro and in vivo. Briefly, circADD2 could directly sponge miR-149-5p, and the level of AKT2, a target gene of miR-149-5p, was downregulated by circADD2. Conclusions: circADD2, as a tumor suppressor in ALL, can sponge miR-149-5p, and may serve as a potential biomarker for the diagnosis or treatment of ALL. Key words: circADD2, ceRNA, miR-149-5p, childhood ALL, AKT2